A microfacies analysis of arid continental carbonates from the Cedar Mesa Sandstone Formation, Utah, USA. (29th November 2019) - Pettigrew, Ross P.; Rogers, Steven L.; Clarke, Stuart M.
Abstract: Arid continental environments are typically dominated by siliciclastic aeolian, alluvial and fluvial deposits. Despite their common recognition within these environments, carbonate deposits are often overlooked, yet they can provide vital insight into the depositional history, climate and tectonic controls of a sedimentary basin. This work presents a detailed microfacies analysis of the carbonates found within the Cedar Mesa Sandstone Formation of the Western USA. The Cedar Mesa Sandstone Formation is an early Permian, predominantly aeolian succession, exposed across much of the Colorado Plateau of southern Utah and northern Arizona. The formation is dominantly clastic erg deposits, that grade into a mixed carbonate/clastic sedimentary succession interbedded with carbonate and evaporitic units, interpreted to represent sabkha or sabkha‐like deposits. While many authors have worked within the aeolian dominated facies and have proposed various facies schemes for the siliciclastic components, comparatively little attention has been paid to the mixed evaporitic/clastic/carbonate aeolian‐sabkha transition zone. In this work the microfacies of the carbonates present within the Cedar Mesa Sandstone are analysed, in order to: (a) develop a record of, and interpret carbonate components, (b) propose depositional mechanisms and (c) identify evolutionary trends that stand alongside the formation's clastic depositional story. Six microfacies are presented: (MF1) Clastic Influenced Carbonate Wackestone; (MF2) Laminated Carbonate Wackestone/Packstone; (MF3) Microbial Laminated Fenestral Bindstone; (MF4) Rounded Mudclast Wackestone; (MF5) Laminated Bioclastic‐Ostracod‐Carbonate Wackestone and (MF6) Microcrystalline Quartz. The microfacies have been interpreted to document the development of carbonate interdune, lacustrine and continental sabkha environments influenced by localized fault control juxtaposed across a wetting and drying climate cycle and provide useful comparisons for other mixed evaporite/carbonate and clastic sequences. Abstract : Carbonate deposits are present in many arid continental basins, however they are often overlooked in favour of clastic deposits, despite giving insight into the depositional history, palaeoenvironmental ecology, climate and/or tectonic controls of a sedimentary basin. This work presents a detailed microfacies analysis of the carbonates found within the Cedar Mesa Sandstone Formation and show how the study of microfacies can better constrain the depositional story of arid continental formations.